Biopsy-proven recurrent, acute, familial hypersensitivity pneumonitis: A case report and literature review. (2018) - Winstone, Tiffany; Hague, Cameron J.; Churg, Andrew; Wright, Joanne L.; Schellenberg, Robert; Ryerson, Chris
Abstract: Hypersensitivity pneumonitis (HP) is characterized by inflammation of the lung parenchyma that is induced by exposure to an inhaled organic antigen. We present a case of recurrent, acute HP caused by repeated transient exposure to a down sleeping bag in a patient with a family history of chronic bird-associated hypersensitivity pneumonitis. The patient's recurrent symptoms, changes in physiology, and radiographic findings coincided with repeated exposure to this source. It was later confirmed that the patient's sister had also developed chronic HP from recurrent exposure to household birds. This case highlights recent studies implicating gene-exposure interactions in the development of HP.